Secondary ovarian neoplasms in a tertiary hospital in South-Western Nigeria (2019)
Background: The ovary is a common site of involvement for metastases constituting 5-30% of all malignant ovarian neoplasms. Over half of these tumours are bilateral. The commonest sources are stomach, large bowel, appendix, breast, uterus (corpus and cervix) and lung. Aim: The aim of this study was to determine the histopathological pattern of metastases to the ovary at the University College Hospital, Ibadan, South western Nigeria. Material and Methods: This was a retrospective study. All histologically confirmed cases of metastases to the ovary from the records and files of the Department of Pathology, University College Hospital (UCH), Ibadan between January 1991 and June 2013 were used for the study. These were cases diagnosed following total abdominal hysterectomy, total abdominal hystero-salpingo oophorectomy, bilateral salpingo-oophorectomy, omentectomy, and multiple peritoneal biopsies and post-mortems at the University College Hospital between January 1991 and June 2013. Cases with inadequate clinical data and whose blocks and or slides could not be retrieved were excluded from the study. The data obtained were analysed using the Statistical Package for Social Sciences version 20 Results: There were 46 cases of metastases to the ovary constituting 5.3% of total ovarian neoplasms. Thirty (63.9%) cases were metastatic carcinomas with the affected patients’ age range of 20-79 years, and peak incidence within the age group of 30-39 years. Nineteen out of 30 cases of metastatic carcinomas were from adenocarcinoma of colon, 6 cases were from the gastric carcinoma while the remaining five cases were from the squamous cell carcinoma of the uterine cervix. Fifteen (31.9%) cases of Burkitt Lymphoma were found with patients with age range of 0-39 years, and the peak age of occurrence at the 2nd decade. The only case of metastatic Malignant Mixed Mullerian Tumour and metastatic Leiomyosarcoma were found in the 3rd and 4th decades of life respectively Conclusion: This study has shown that metastases to the ovary occur in younger age groups in our environment. Therefore this study emphasizes that in young females with ovarian masses, the likelihood of metastatic tumours should not be discarded because, correct and precise diagnosis of secondary ovarian malignancy is critical as it has significant implication on the patients’ choice of management and prognosis.